2016
DOI: 10.21276/aimdr.2016.2.4.57
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of Estimation of Stature from Index Finger Length in Indian Population

Abstract: Background: Estimation of stature is basic and major section of Anthropological research which is necessary for unmistakable conformation and is used by medico-legal experts, forensic examiners and Anatomists. Methods: In the present, morphometric, cross sectional study of the measurement of stature from index finger length among the population of India is done. This study consist of 400 subject among them 200 are males and 200 females between the age group of 17-25 year. The subjects are students of Teerthank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Davangere district, Karnataka, India, Bardale R V et al in Maharashtra population in India. 1,5,7,[14][15][16][17][18] Gender difference in index finger length in this study also showed highly significant (p<0.001) and male index finger length was longer than female index finger length. Balachandran…”
Section: Original Articlementioning
confidence: 60%
See 1 more Smart Citation
“…Davangere district, Karnataka, India, Bardale R V et al in Maharashtra population in India. 1,5,7,[14][15][16][17][18] Gender difference in index finger length in this study also showed highly significant (p<0.001) and male index finger length was longer than female index finger length. Balachandran…”
Section: Original Articlementioning
confidence: 60%
“…In case of complete or incomplete identification of individuals, height measurements are considered an important parameter. 1 Height measurements and other parts of the individual have a constant relationship and based on this principal, anthropologist and forensic experts use height parameter in identification purpose. 2 Charak and Sushruta, who were ancient time physician and surgeon also found the relationship between height and different body parts.…”
Section: Introductionmentioning
confidence: 99%
“…Next to pelvic bones, the human cranium is regarded as the best sex indicator. 4 Craniometry is the measuring of the skull that is done scientifically and is useful in anthropometry and forensics. 5 Numerous cephalic indices are frequently employed to measure racial and gender differences and offer a framework for metrical recording of cranial feature sizes and proportions.…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirm earlier findings that the CI was considerably higher in the female crania compared to the male crania. 4,9 According to Williams et al (2000) the skulls are divided into four types based on cranial index as follows, Dolicocephalic (CI<74.9), Mesocephalic (CI=75 to 79.9), Brachycephalic (CI=80 to 84.9), Hyperbrachycephalic (CI=85 to 89.9). 10 However, several studies discovered that men had higher CI than women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation